2017
DOI: 10.1209/0295-5075/119/56001
|View full text |Cite
|
Sign up to set email alerts
|

Control of a single-particle localization in open quantum systems

Abstract: We investigate the possibility to control localization properties of the asymptotic state of an open quantum system with a tunable synthetic dissipation. The control mechanism relies on the matching between properties of dissipative operators, acting on neighboring sites and specified by a single control parameter, and the spatial phase structure of eigenstates of the system Hamiltonian. As a result, the latter coincide (or near coincide) with the dark states of the operators. In a disorder-free Hamiltonian wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…The switch from diffusive to ballistic propagation for non-zero α can be understood as an interplay between disorder and dissipation. As we already pointed it out, dissipation selects Anderson modes from a particular part of the spectrum, and they borrow spatial phase properties of the zero-disorder plain wave eigenstates, with wave numbers 16,32 k ≈ α. Overlapping in space (Figs. 1 and 2), the exponentially localized modes interact due to dissipative coupling.…”
mentioning
confidence: 86%
See 3 more Smart Citations
“…The switch from diffusive to ballistic propagation for non-zero α can be understood as an interplay between disorder and dissipation. As we already pointed it out, dissipation selects Anderson modes from a particular part of the spectrum, and they borrow spatial phase properties of the zero-disorder plain wave eigenstates, with wave numbers 16,32 k ≈ α. Overlapping in space (Figs. 1 and 2), the exponentially localized modes interact due to dissipative coupling.…”
mentioning
confidence: 86%
“…Second, it was shown that a one-dimensional quantum system with a Hamiltonian exhibiting Anderson localization can be driven into a steady state, an "Anderson attractor", which retains localization properties 15 . Such an asymptotic state can be engineered with a set of local dissipative operators [17][18][19][20] , the corresponding mechanism is based on the robust spatial phase-structure of Anderson modes 16 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Decoherence will generally allow initially localized states to expand as destructive interference is lifted [4,5]. The details of such dynamics [6] and their stationary solutions [7,8] depend on the specific properties of the environment coupling, as encoded, for example, in a Lindblad operator. Quite generically, decoherence rates are particularly high for states that can easily be distinguished by the environment, whereas they tend to be low for states that can hardly be distinguished by the environment.…”
mentioning
confidence: 99%